Spatiotemporal variations and implications of luminescence sensitivity of quartz grains on the Chinese Loess Plateau since the last interglaciation. Issue 1 (January 2021) - Lü, Tongyan; Sun, Jimin; Feathers, James K.; Sun, Dongxia
Abstract: Although luminescence sensitivity of quartz grains of desert sands has been used in discriminating provenance, it still remains unclear about its spatiotemporal variations and climatic implications. In this paper, the luminescence sensitivity of quartz grains from the northern margin of the Chinese Loess Plateau (CLP) was studied using single-aliquot optically stimulated luminescence (OSL) and "pseudo" single-grain OSL measurements. Our results indicate that the OSL sensitivities have lower values in sand/loess beds and higher values in paleosols. We suggest that the variations in OSL sensitivity of quartz grains with depth on the CLP are mainly influenced by the origin of the quartz grains as they are related to the loess-sized material production processes and the migration of desert regions. More quartz grains of glacial origin with lower luminescence sensitivity, together with the reduced durations of irradiation and exposure cycles induced by shorter transport distance due to desert expansion, account for the lower luminescence sensitivity of glacial periods. Moreover, both the mountain processes and the retreat–advance of deserts are ultimately related to climatic changes, therefore, the orbital scale variations of luminescence sensitivity are controlled by glacial–interglacial oscillations on the CLP.